Iatrogenic ureteric injury during abdominal or pelvic surgery: a meta-analysis - Yanagisawa, Takafumi; Mori, Keiichiro; Quhal, Fahad; Kawada, Tatsushi; Mostafaei, Hadi; Laukhtina, Ekaterina; Rajwa, Pawel; Sari Motlagh, Reza; Aydh, Abdulmajeed; König, Frederik; Pallauf, Maximilian; Pradere, Benjamin; et al. (BJU international, 2023)
OBJECTIVE: To assess the incidence of ureteric injuries, clinical value of prophylactic ureteric stenting and impact of intra- or postoperative detection of ureteric injuries in patients treated with gynaecological or colorectal surgery. METHODS: Multiple databases were searched for articles published before September 2021 according to the Preferred Reporting Items for Systematic Review and Meta-Analyses statement. Studies were deemed eligible if they evaluated the differences in the rate of ureteric injuries between laparoscopic and open surgery, prophylactic ureteric stenting or not, and those of final treatment success between intra- and postoperative detection in patients who underwent gynaecological or colorectal surgery. RESULTS: Overall, 46 studies were eligible for this meta-analysis. Compared to open surgery, laparoscopic hysterectomy was associated with a higher incidence of ureteric injuries (pooled odds ratio [OR] 2.12, 95% confidence interval [CI] 1.71-2.62), but there was no statistically significant difference in colectomy (pooled OR 0.89, 95% CI 0.77-1.03). Prophylactic ureteric stenting was associated with a lower incidence of ureteric injuries during gynaecological surgery (pooled OR 0.61, 95% CI 0.39-0.96). The number needed to perform ureteric stenting to prevent one ureteric injury was 224 in gynaecological surgery. On the other hand, prophylactic ureteric stenting did not reduce the risk of ureteric injuries during colorectal surgery. Intraoperative detection of a ureteric injury was associated with a lower rate of complication management failure compared to postoperative detection (pooled OR 0.22, 95% CI 0.12-0.41). CONCLUSIONS: Laparoscopic hysterectomy seems to be associated with a higher rate of ureteric injuries compared to an open approach. Prophylactic ureteric stenting seems to reduce this risk during gynaecological surgery. Intraoperative detection of a ureteric injury during abdominal/pelvic surgery improves outcomes, suggesting the need for awareness and proactive problem identification. Further well-designed studies assessing the candidates who are more likely to benefit from prophylactic ureteric stenting including cost analysis are needed.
Keywords: ureteric injury; Humans; #UroTrauma; laparoskopie; ureter; #Urology; Gynecologic Surgical Procedures; urologické nemoci; ureteric stent; gynekologické chirurgické výkony; Female; lidé; hysterectomy; colectomy; laparoscopic; iatrogenic; ženské pohlaví; Urologic Diseases; Laparoscopy; iatrogenní nemoci; Iatrogenic Disease; Ureter